Fusion of the Lumican (LUM) Gene With the Ubiquitin Specific Peptidase 6 (USP6) Gene in an Aneurysmal Bone Cyst Carrying a t(12;17)(q21;p13) Chromosome Translocation - PANAGOPOULOS, IOANNIS (Cancer Genomics Proteomics, 2020)
Background/Aim: Aneurysmal bone cyst is a benign bone lesion with a strong tendency to recur. The rearrangement of chromosome band 17p13/USP6 gene is now considered a characteristic genetic feature of aneurysmal bone cyst, with t(16;17)(q22;p13)/CDH11-USP6 as the most frequent chromosomal aberration/fusion gene. We report a novel variant translocation leading to a new fusion gene in an aneurysmal bone cyst. Materials and Methods: Genetic analyses were performed on an aneurysmal bone cyst found in the tibia of a child. Results: G-banding chromosome analysis yielded the karyotype 46,XX,t(12;17)(q21;p13)[5]/46,XX[2]. FISH analysis with a USP6 break-apart probe showed rearrangement of USP6. RNA sequencing detected LUM-USP6 and USP6-LUM fusion transcripts which were subsequently verified by RT-PCR/Sanger sequencing. The two genes exchanged 5’- non-coding exons. Thus, promoter swapping between USP6 and LUM had taken place. Conclusion: We report a novel t(12;17)(q21;p13) chromosome translocation which gave rise to a LUM-USP6 fusion in an aneurysmal bone cyst.